2019
DOI: 10.5194/gmd-2019-91
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replicability of the EC-Earth3 Earth System Model under a change in computing environment

Abstract: Abstract. Most Earth System Models (ESMs) are running under different high-performance computing (HPC) environments. This has several advantages, from allowing different groups to work with the same tool in parallel to leveraging the burden of ensemble climate simulations but also offering alternative solutions in case of shutdown (expected or not) of any of the environments. However, for obvious scientific reasons, it is critical to ensure that ESMs provide identical results under changes in computing environ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Also, Baker et al [1] have used their approach to identify issues with certain compilers on certain machines. Massonnet et al [9] also applied their index based test as they ported their model to a new machine. We plan to apply the new multivariate tests for such real world scenarios in the near future, which will also help establish an optimum balance between the false positive and false negative rates of the tests.…”
Section: Summary Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Baker et al [1] have used their approach to identify issues with certain compilers on certain machines. Massonnet et al [9] also applied their index based test as they ported their model to a new machine. We plan to apply the new multivariate tests for such real world scenarios in the near future, which will also help establish an optimum balance between the false positive and false negative rates of the tests.…”
Section: Summary Discussion and Future Workmentioning
confidence: 99%
“…Mahajan et al [7,8] applied a testing approach where they also compare short (1 yr) ensembles (about 30 members) of the control as well as the perturbed simulation to evaluate if the climate statistics of the two ensembles are statistically similar by evaluating the global annual average of each model output variable separately. Massonnet et al [9] compare the distribution of a normalized index of 13 variables to evaluate the reproducibility of a fully coupled model using 5member ensembles of 20-yr simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For scenario MIP, we select three available climate model data with high spatial resolution, namely BCC-CSM2-MR (Wu et al 2019), EC-Earth3 (Massonnet et al 2019) and MPI-ESM1-2-HR (Gutjahr et al 2019), the basic information of which is shown in Table 1. Since the second aspect of this study is mainly to compare the differences of the three calibration strategies in streamflow prediction, the daily scale precipitation, minimum and maximum temperatures of the three climate models for 2021-2050 are analyzed.…”
Section: Climate Model Datamentioning
confidence: 99%
“…However, the cray reproducibility tests did not pass and therefore the EC-Earth consortium was advised to use the intel compilers in place of cray compliers on the ECMWF system. The EC-Earth reproducibility protocol was designed by the EC-Earth community (Massonnet et al, 2019) to assess the reproducibility of the EC-Earth model system. This protocol is based on a statistical comparison of standard climate metrics derived from multi-ensembles of multi-decadal control integrations executed in different HPC environments.…”
Section: Implementation Of Ec-earth On Ichec and Ecmwf Supercomputing Systemsmentioning
confidence: 99%